2018
DOI: 10.1007/s00414-018-1905-6
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging of third molars in forensic age estimation: comparison of the Ghent and Graz protocols focusing on apical closure

Abstract: Imaging modality-specific and MRI sequence-specific reference data are needed in age estimation. A higher in-plane resolution and a bite bar increase assessability of apical closure, whereas they do not affect stage allocation of assessable apices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
4

Year Published

2019
2019
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 28 publications
0
11
0
4
Order By: Relevance
“…For other structures, pooling the data of different studies might address this issue, but before this is done, it needs to be ascertained whether or not it is safe to pool data obtained with different MR-sequences. After all, it has been demonstrated that age distributions within stages might differ between sequences for third molars [15] and for the left wrist (Fig. 2) [47].…”
Section: Study Populations and Magnetic Resonance Imaging Approachesmentioning
confidence: 96%
See 2 more Smart Citations
“…For other structures, pooling the data of different studies might address this issue, but before this is done, it needs to be ascertained whether or not it is safe to pool data obtained with different MR-sequences. After all, it has been demonstrated that age distributions within stages might differ between sequences for third molars [15] and for the left wrist (Fig. 2) [47].…”
Section: Study Populations and Magnetic Resonance Imaging Approachesmentioning
confidence: 96%
“…When measurements were made, the way of obtaining them should be described clearly. It was considered inappropriate to compare the age distributions within developmental stages based on MRI with those based on radiographs, since it has been demonstrated that imaging technique specific reference data are required [14][15][16][17][18][19].…”
Section: Types Of Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…19 Indeed, the only comparative study between MRI approaches of different centers concluded that MR-sequence-specific reference studies should be applied because the detection of small changing details such as the closing of the apex can be affected by MR-sequence parameters. 66 Similarly, De Tobel et al reported an inferior age estimation performance when the model based on wrist T1 turbo spin-echo MRI was applied to T1 volumetric interpolated breath-hold examination (VIBE) MRI data and vice versa. 14 The next step in MRI for age estimation appears to be studying if the MRI data from different groups can safely be merged.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 98%
“…Parts of the study population have been included in earlier publications on SSA [23,24,27,[34][35][36][37]. All participants gave informed consent, and in minors, the parents also consented.…”
Section: Study Populationmentioning
confidence: 99%